Upaya Guru dalam Menanamkan Pendidikan Karakter Peduli Lingkungan Pada Siswa Kelas 4 di MI Hidayatul Mubtadi’in 1 Cibeber - Eva Muarofah; Frenky Mubarok; Sanuri Sanuri (Khulasah : Islamic Studies Journal, 2022)
Character education is an attitude and action that always tries to prevent damage to the surrounding natural environment, and develops efforts to repair the damage to nature that has already occurred. The problem in this study is that even though environmental care activities have been implemented, there is still a lack of student interest in caring for the environment resulting in students becoming less responsible and disciplined. This study aims to describe the efforts of teachers in instilling environmental care character education at Madrasah Ibtidaiyah Hidayatul Mubtadi'in 1 Cibeber. The subjects of this study were grade 4 students at the Hidayatul Mubtadi'in 1 Cibeber Elementary School, Sukagumiwang District, Indramayu Regency. The object of this research is character education that cares for the environment. Data collection techniques using observation techniques, interviews and documentation. The results of research through observation and interviews show that grade 4 students' environmental awareness has shown concern for the school environment and maintaining personal hygiene. This can be seen from the state of the class and school which is clean and tidy. Here it is clear that students' concern for the environment can influence the moral formation of students, especially moral discipline and responsibility in protecting and caring for the environment. Obstacles faced by teachers in instilling environmental care character education for grade 4 students at MI Hidayatul Mubtadi'in 1 Cibeber School are student habits and exemplary behavior. This can be seen from the fact that there are still some students who do not care about the school environment. Obstacles related to student habits are that students still have to be reminded by the teacher in their implementation. The obstacle related to exemplary is that the teacher has not provided exemplary thoroughly to students, both time, place and situation.